PHYSIOLOGICAL OBSERVATIONS ON SUBARCTIC BEARS UNDER WINTER DEN CONDITIONS. - Folk Jr, G. Edgar; simmonds,Richard C.; Folk,Mary A. (1966)
Heart rates, body temperature, and urinary output were studied in a variety of activity states in one or all of a group of four bears (two grizzly bears, Ursus horribilis, and two black bears, Ursus americanus Pallas). In addition, the cardiac activity of three black bears was studied during whole body hypothermia. The resting heart rates obtained during winter dormancy from three bears were significantly lower (75-91%) than those obtained during the summer. The physiological activity cycle of the dormant bears did not change appreciably as they continued to show a relatively high heart rate (40 beats/minute) in the morning hours. Body temperatures obtained from one black bear during winter dormancy showed only a 4C depression. One dormant bear did not urinate for at least three months, and it was not until the third day post-arousal that voiding occurred. The three black bears subjected to whole body hypothermia experienced asystole and cardiac arrest at body temperatures of 16 - 21C. At the time of cardiac arrest, heart rates as low as 1 beat/minute were recorded, indicating that bears could maintain low hypothermic heart rates. (Author)